Effect of Volatile Reactions on the Thermochemical Conversion of Biomass Particles. (May 2017) - Fatehi, Hesameddin; Qu, Zhechao; Schmidt, Florian M.; Bai, Xue-Song
Abstract: A numerical and experimental study on the conversion of a biomass particle is carried out to quantify the effect of homogeneous volatile combustion on the biomass pyrolysis. The numerical domain consists of a particle and its surrounding and the model considers detailed chemical kinetic mechanism for reaction of pyrolysis products. A detailed pyrolysis model is employed which provides the composition of pyrolysis products. The effect of gas phase reaction on the conversion time and temperature of the particle is analyzed and it was shown that the gas phase reactions results in shorter pyrolysis time. H2 O mole fraction and temperature above a biomass pellet from wheat straw (WS) and stem wood (SW) were experimentally measured using tunable diode laser absorption spectroscopy (TDLAS) while recording the particle mass loss. The TDLAS data were used to validate the numerical model developed for biomass conversion. The results showed that by considering the gas phase reactions a good agreement between the measurement and the model prediction for mass loss and temperature can be achieved. For H2 O mole fraction on top of the particle, on the other hand, some discrepancy between the model prediction and the experimental data was observed. Nevertheless, the difference in H2 O mole fraction would be much larger by neglecting the gas phase reaction at the particle boundary.